Etika Islam dalam Menyikapi Tantangan Pendidikan Abad ke-21 - Jamil, Jamil; Maraina, Maraina; St. Nurhayati Ali; Muhammad Nur Maallah (Journal of Humanities, Social Sciences, and Education, 2026)
21st-century education faces complex challenges due to rapid technological developments, globalization, and changing patterns of social interaction, which require character formation based on moral and ethical values. This study aims to analyze the role of Islamic ethics in addressing the dynamics of modern education through a literature study approach. Data were collected from Islamic education textbooks, national and international journal articles, and educational policy documents. The results of the study indicate that Islamic ethical values ​​such as honesty (ṣidq), trustworthiness (amanah), justice (‘adl), responsibility (mas’uliyyah), and moderation (wasathiyah) are highly relevant in shaping the character of intelligent, adaptive, and virtuous students. Islamic ethics provides guidelines for the wise use of digital technology, addressing the impact of globalization, and fostering social awareness and ecological awareness. The holistic integration of ethical values ​​into the curriculum, learning methods, and school culture is crucial to ensure education produces individuals with character and noble morals. This study concludes that Islamic ethics is not merely a normative norm, but also a practical strategy in modern, humanistic, and sustainable education. The implications of this research encourage the implementation of Islamic values-based education integrated with digital literacy, 21st-century skills, and comprehensive student character development.